A Review of the Empirical Ethical Decision-Making Literature: 2004–2011 - Craft, Jana L. (2013)
This review summarizes the research on ethical decision-making from 2004 to 2011. Eighty-four articles were published during this period, resulting in 357 findings. Individual findings are categorized by their application to individual variables, organizational variables, or the concept of moral intensity as developed by Jones (Acad Manag Rev 16(2):366–395, 1991). Rest’s (Moral development: advances in research and theory, Praeger, New York, 1986) four-step model for ethical decision-making is used to summarize findings by dependent variable—awareness, intent, judgment, and behavior. A discussion of findings in each category is provided in order to uncover trends in the ethical decision-making literature. A summary of areas of suggested future research is provided.
Keywords: Literature Review; Moral Intensity; Rest’s model; Intent; Judgment; Behavior; Awareness; ethical decision-making